Predicting the Effect of Magnetic Acquisition Using CrowdMag Android App on Fundamental Magnetic Concepts Mastery in Basic Physics - Jufri; Rizky Fatmalasari L; La Naston (Jurnal Penelitian Pendidikan IPA, 2024)
If the concept of the magnetic field is categorized as one of the physics concepts considered difficult by some students, then classroom instruction itself is not sufficient to explain it. This research reveals that integrating magnetic acquisition using the Android application CrowdMag in learning the concept of the magnetic field can be an effective solution. Testing 32 (on thirty-two) Faculty of Teacher Training and Education (FKIP) Universitas Darussalam Ambon students showed that magnetic acquisition using the Android application CrowdMag had a significant effect on the mastery of the magnetic field concept. This effect is not due to chance, as evidenced by a significant regression coefficient β and an F-calculated value greater than the F-table value, as well as a strong and linear correlation between the variables of magnetic acquisition and the mastery of the magnetic field concept. The resulting regression model (Y = 31.271 + 0.584X) can be used to predict the effect of magnetic acquisition using the Android application CrowdMag on the mastery of basic physics concepts of magnetic fields for students of FKIP Unidar Ambon.